2020
DOI: 10.1038/s41598-020-70416-0
|View full text |Cite
|
Sign up to set email alerts
|

Modelling water levels of northwestern India in response to improved irrigation use efficiency

Abstract: The groundwater crisis in northwestern India is the result of over-exploitation of groundwater resources for irrigation. The Government of India has targeted a 20 percent improvement in irrigation groundwater use efficiency. In this perspective, and using a regional-scale calibrated and validated three-dimensional groundwater flow model, this article provides the first forecasts of water levels in the study area up to the year 2028, both with and without this improvement in use efficiency. Future water levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Daccache et al 22 projected that a pressurized irrigation system is capable to increase irrigation efficiency, but CO 2 emissions increase due to additional energy consumption compared to a gravity-fed surface irrigation system. Shekhar et al 23 showed that technology changes could have the potential to mitigate groundwater depletion through pressure reduction on water resources. However, the lower percolation from fields with improved water saving irrigation techniques may reduce aquifer recharge 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Daccache et al 22 projected that a pressurized irrigation system is capable to increase irrigation efficiency, but CO 2 emissions increase due to additional energy consumption compared to a gravity-fed surface irrigation system. Shekhar et al 23 showed that technology changes could have the potential to mitigate groundwater depletion through pressure reduction on water resources. However, the lower percolation from fields with improved water saving irrigation techniques may reduce aquifer recharge 24 .…”
Section: Introductionmentioning
confidence: 99%
“…In terms of groundwater balance, the aquifer of High Plains in the US shows a water table decline rate of about 0.8 m per year (Dong et al 2019). Moreover, the decline in the groundwater level is reported by 2.8 m per year in the northwestern region of India (Shekhar et al 2020). More specifically, the MENA region is a water resource scarcity area that is experiencing serve implications of climate change that extremely impact the recharge of the groundwater resources (Lattemann & Höpner 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Such improvements in efficiency are possible as part of a second Green Revolution that incorporates adoption of an integrated genetic and natural resource management approach (Rockström 2003, Senapati andSemenov 2020). The first Green Revolution in the 1960s largely focused on irrigated ecologies, but the second Green Revolution needs to focus on both irrigated and dryland systems with enhanced resource use efficiency (Davis et al 2017, Shekhar et al 2020. Drylands in India are facing a number of challenges including water scarcity, land degradation, malnutrition, and poverty.…”
Section: Introductionmentioning
confidence: 99%